Mechanistic Pathogenesis of Endothelial Dysfunction in Diabetic Nephropathy and Retinopathy - Yang, Jing; Liu, Zhangsuo (Frontiers in Endocrinology, 2022)
Diabetic nephropathy (DN) and diabetic retinopathy (DR) are microvascular complications of diabetes. Microvascular endothelial cells are thought to be the major targets of hyperglycemic injury. In diabetic microvasculature, the intracellular hyperglycemia causes damages to the vascular endothelium, via multiple pathophysiological process consist of inflammation, endothelial cell crosstalk with podocytes/pericytes and exosomes. In addition, DN and DR diseases development are involved in several critical regulators including the cell adhesion molecules (CAMs), the vascular endothelial growth factor (VEGF) family and the Notch signal. The present review attempts to gain a deeper understanding of the pathogenesis complexities underlying the endothelial dysfunction in diabetes diabetic and retinopathy, contributing to the development of new mechanistic therapeutic strategies against diabetes-induced microvascular endothelial dysfunction.